2021
DOI: 10.3390/cancers13122967
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Local and Systemic Control between Partial- and Whole-Breast Radiotherapy in Low-Risk Breast Cancer—A Meta-Analysis of Randomized Trials

Abstract: Purpose/Objective: The standard treatment for localized low-risk breast cancer is breast-conserving surgery, followed by adjuvant radiotherapy and appropriate systemic therapy. As the majority of local recurrences occur at the site of the primary tumor, numerous trials have investigated partial-breast irradiation (PBI) instead of whole-breast treatment (WBI) using a multitude of irradiation techniques and fractionation regimens. This meta-analysis addresses the impact on disease-specific endpoints, such as loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 114 publications
0
6
0
Order By: Relevance
“…NSMRH can be successfully combined with RT to prevent local recurrence and metastasis by being implanted locally in the resection site of a breast tumor and steadily producing nano-su with high MMP secretion. Local recurrence and distant metastasis receiving RT in breast cancer become major causes for tumor progression ( Li W et al, 2021 ; Haussmann et al, 2021 ). The molecular mechanism may be as follows: (1) the remnants of tumor tissue gradually proliferated due to neovascularization ( Giatromanolaki et al, 2002 ; Arora and Cascella, 2021 ); (2) The subsets of cancer cells might be resistant to radiation ( Bernichon et al, 2017 ; Mal et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…NSMRH can be successfully combined with RT to prevent local recurrence and metastasis by being implanted locally in the resection site of a breast tumor and steadily producing nano-su with high MMP secretion. Local recurrence and distant metastasis receiving RT in breast cancer become major causes for tumor progression ( Li W et al, 2021 ; Haussmann et al, 2021 ). The molecular mechanism may be as follows: (1) the remnants of tumor tissue gradually proliferated due to neovascularization ( Giatromanolaki et al, 2002 ; Arora and Cascella, 2021 ); (2) The subsets of cancer cells might be resistant to radiation ( Bernichon et al, 2017 ; Mal et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the trial protocol mandated standard tangential irradiation, a subsequent retrospective analysis of 228 patients showed that more than half of the patients were treated with high tangents and 15% received supraclavicular irradiation [ 13 ]. A meta-analysis of prospective partial breast irradiation-trials demonstrated an increased risk of axillary recurrences with an odds ratio of 1.75 (95%-confidence interval 1.07–2.88), further suggesting that incidental axillary irradiation might contribute to locoregional control [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, telangiectasia and mild breast fibrosis are significantly higher in the APBI group although the fibrosis related to APBI is low grade and limited to the tumor bed and doesn't significantly affect overall cosmetics. Actually, published randomized controlled trials have shown inconsistent outcomes [24]. Recent meta-analysis has shown that APBI compared to WBI has similar toxicity side effects and cosmetic effects [25].…”
Section: Discussionmentioning
confidence: 99%